Disentangling the drivers of context‐dependent plant–animal interactions. (1st September 2014) - Maron, John L.; Baer, Kathryn C.; Angert, Amy L.; Lau, Jennifer
Summary A fundamental goal of ecology is to predict how strongly one species affects the abundance of another. However, our ability to do so is hindered by the fact that interaction outcomes are notoriously variable in space and time (i.e. context‐dependent) and we lack a predictive understanding of the factors that drive this context‐dependence. Determining whether abiotic factors, in particular, predictably shift the outcome of species interactions is of critical importance for many contemporary problems, from forecasting climate change impacts to predicting the efficacy of weed biocontrol. In this essay, we highlight the context‐dependent nature of interactions between plants and their pollinators and herbivores. We advocate for approaches that will identify whether particular abiotic factors predictably shift how strongly these interactions influence plant abundance and/or population growth. We review long‐standing theory that describes how abiotic context should influence the selective impacts of pollinators and herbivores on plants and articulate why this theory requires modification to predict population‐level effects. Finally, we propose several empirical approaches to address gaps in existing knowledge: (i) experiments across broad abiotic gradients to determine whether the outcome of interactions between pollinators or herbivores and plants varies consistently with changing abiotic conditions; (ii) experiments that manipulate the underlying environmental gradient to elucidate whether the abiotic factor that correlates with interaction outcome is causal; and (iii) seed addition studies to explore how strongly seedling recruitment correlates with seed input (as affected by pollen limitation or herbivory) and to quantify how the strength of the seed‐to‐seedling linkage is influenced by the underlying abiotic gradient. Synthesis. Our understanding of the underlying drivers of context‐dependent plant–animal interactions is currently not well developed. Progress in this area is essential to better predict when and where species interactions will alter the responses of plant populations to environmental changes as well as to develop more robust theory. Experiments aimed at explicitly exploring the role of abiotic factors in mediating the population‐level impact of pollen limitation and herbivory could determine the extent to which variation in the abiotic environment predictably shifts the outcome of these interactions.